Validity Of Some International Rainfall Erosivity Models For Mosul Climatic Condition at Northern Iraq (NTU Journal of Agriculture and Veterinary Science, 2021)
The main purpose of this study was to estimate the rainfall erosivity index ( R ) of USLE for eight models to get on the most appropriate erosivity index that can be used for climatic condition of Mosul city / northern Iraq . The validity of the models has been evaluated using the monthly rainfall depth for the period of (1983 – 2012 ) .Results showed that there is a wide variation in R value among the models. It ranged from ( 59.5 ) to ( 624.8 ) MJ.mm .ha-1.hr-1 .The reason for that may be to the variation in the basic formula of each model in estimating the errosivity index . . Statistical analysis using MAD, MSD and SE indicate that the Arnoldus model produced better predictions of erosivity at a given output time scale and generated better results than the other models. So it can be justified to use this model in future studies if required for describing the rainfall erosivity under regional climate of Mosul watershed.